Shelter from the Storm: Using Jurisdictional Statutes to Protect Victims of Domestic Violence after the Violence against Women Act of 2000 - Goelman, Deborah M. (Columbia Journal of Gender and Law, 2004)
Domestic violence fuels many of the nation’s bitterly contested interstate custody cases. It is an underlying issue in most parental abduction cases, which occur at an estimated rate of 203,900 per year. Despite the role of domestic abuse in interstate custody cases, in the past, legislators enacted jurisdictional laws to prevent forum-shopping and parental abduction without considering their impact on domestic violence survivors. In recent years, jurisdictional laws such as the Parental Kidnapping Prevention Act and the Uniform Child Custody Jurisdiction and Enforcement Act have begun to incorporate safety provisions for victims of domestic violence. Full faith and credit laws, including provisions in the Violence Against Women Act and the Violence Against Women Act of 2000, have been drafted for the primary purpose of protecting victims who flee across state or tribal lines. This article will review the relevant state and federal laws and demonstrate that courts and family law attorneys may apply these jurisdictional statutes with a view to protecting domestic violence survivors and children embroiled in interstate custody cases. The article begins with an examination of how the United States legal system has historically addressed domestic violence and then discusses the current responses of the criminal and civil justice systems. Part I also provides readers with a contemporary overview of issues related to domestic violence survivors’ flight across state lines. These include the dangers of separation violence when victims leave their abusers, the impact of domestic violence on children, and the potential protection that relocation offers many victims.